Effectiveness of modular training at Farmers’ Training Center: The case of Fogera District, Amhara National Regional State, Ethiopia - Mekuria, Wolde (Haramaya University, 2010)
Subsistence farming, climatic change, environmental degradation and low adult literacy ratio are problems of livelihoods. To increase productivity and alleviate poverty in rural areas, farmers need to have training to improve knowledge, attitudes and skills on better farming practices. Attending modular training might lead farmers to produce market oriented commodities. Such trainings are offered in the Farmers’ Training Centers, which are being functional at Peasant Association level throughout Ethiopia. The objectives of the study were to analyze whether modular training addresses the knowledge gap of the farmers and enable them to use the acquired knowledge; institutional linkages and positive deviances of FTCs in performance and their contributions. A total of 120 respondents were selected. Interview schedules, focused group discussions, key informant interviews, personal observations and case studies were conducted for quantitative and qualitative data collection. RAAKS tools, SWOT analysis, Likert scale and teacher-made-test tools were also employed. The data were analyzed using descriptive statistical tools like, percentage, frequencies, chi-square and t-test. The result of the study revealed that, in the study area, Fogera, 7 PAs had delivered modular trainings. Even though, the training time and season was sufficient and convenient, less participation of females and being more theoretical and lecture type of methodology of the training were the major deficiencies. But trained farmers acquired better knowledge, skill, and attitude significantly than untrained farmers. Actors have been identified with different intensity of linkages. Many development actors assessed as strong, medium, weak and no linkage among and between them. The study indicated that, it requires enhancing the linkage of actors and their roles involved in training system. There are actors missed to support and integrate FTCs such as, Fogera Wet-land project, GTZ, CARE, private investors, research centers and ORDA. Positive deviances of FTCs were assessed, and found that there were no as such significant deviations documented at FTC level. Case studies and key informants revealed that, there are individual smallholder farmers who could perform and emerge better than the others as positive deviants and raised their level of living that could be scaled-up.